Fuzzy logic prediction of dengue hemorrhagic fever distribution in pringsewu region - Muslihudin M.; Mukodimah S.; Dwiyana E.; Trisnawati; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Dengue Hemorrhagic Fever (DHF) has been a public health problem in Indonesia for the past 47 years. Dengue hemorrhagic fever or dengue fever is an infection caused by the dengue virus, which is transmitted by the bite of the female Aedes aegipty or female Aedes albopictus. This study was conducted to predict the distributin of dengue hemorrhagic fever in pringsewu areas using fuzzy logic method. Fuzzy logic method was selected because it is able to select the best alternative from all available alternatives. In this study seven criteria were used as reference in predicting the distribution of dengue hemorrhagic fever in pre-pregnancy area such criteria as Population Density, air humidity, water sources, health facilities, sanitation, sewerage and trash cans. In addition to the criteria also used the weighting criteria to determine the best alternative and from the calculation obtained the highest score found in column d which means that the area or village with Indication as in column d was an area prone to the distribution of dengue fever, while the lowest score was in the column y which means that the area with Indication column y was the area with the least chance of risk of dengue hemorrhagic fever distribution. BEIESP.